2010
DOI: 10.2131/jts.35.773
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood parameters in pregnant Japanese White rabbits

Abstract: -Changes in blood parameters, especially those related to blood coagulations, were examined on gestational days (GDs) 6, 18 and 28 in Japanese White rabbits. As compared with the non-pregnant group, the following changes were observed in the pregnant group. For blood coagulation-related parameters, fibrinogen, platelets and antithrombin time III (ATIII) was significantly increased on GD 18 and/or GD 28, and activated partial thromboplastin time (APTT) was significantly prolonged on GDs 18 and 28. For the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
3
5
0
Order By: Relevance
“…In present study, the maternal blood glucose was significantly decreased during gestation in comparison with that of the non-pregnant blood serum, which is almost in accordance with those most recently reported in pregnant New Zealand white and Japanese white rabbits [22,29]. Change of maternal glucose concentration during gestation may reflect glucose supply or replenishment according to nutritional demand for the rabbit development [43].…”
Section: Discussionsupporting
confidence: 92%
“…In present study, the maternal blood glucose was significantly decreased during gestation in comparison with that of the non-pregnant blood serum, which is almost in accordance with those most recently reported in pregnant New Zealand white and Japanese white rabbits [22,29]. Change of maternal glucose concentration during gestation may reflect glucose supply or replenishment according to nutritional demand for the rabbit development [43].…”
Section: Discussionsupporting
confidence: 92%
“…Due to this condition in the captive production of this animal of that study there was food supplementation during this period, which may be related to this serum glucose increase in this phase. In rabbits the glucose serum levels fall near to parturition in the final third of pregnancy due to rapid fetal growth in the last weeks of pregnancy, and may even be related to the lactation peak, with the uptake of this metabolite by the mammary gland for lactose synthesis (HANEDA et al, 2010;MIZOGUCHI et al, 2010). The initial hypoglycemia in pregnant sheep is described as pregnancy toxemia (SANTOS et al, 2011) and this fact corroborates our study since during pregnancy in agoutis (Figure 2) no pathological changes were observed.…”
Section: Discussionsupporting
confidence: 88%
“…Litter size can range between 4 and 12 kits, depending on the breeding program and genetic background (Foote & Carney, 2000;López-Tello et al, 2015;López-Tello, Arias-Álvarez, Jiménez-Martínez, Barbero-Fernández et al, 2017). Due to their size, serial blood collections of the rabbit doe can be performed to inform of the endocrine and metabolic changes during pregnancy (Haneda et al, 2010;López-Tello, Arias-Álvarez, Jiménez-Martínez, Barbero-Fernández et al, 2017). Moreover, ultrasound imaging of the developing conceptus can be undertaken to assess longitudinal changes with subsequent follow up of the offspring (Chavatte-Palmer et al, 2008;López-Tello et al, 2015;López-Tello, Arias-Álvarez, Jiménez-Martínez, Barbero-Fernández et al, 2017;Osmanski et al, 2015;Polisca, Scotti, Orlandi, Brecchia, & Boiti, 2010).…”
Section: Reproductive Characteristics Of the Rabbitmentioning
confidence: 99%